The Influence of Company Internal and External Factors on Audit Delay (Study on Bei-Registered Manufacturing Companies 2019-2021) - Eni Indriani; Nungki Kartikasari (LPPM Institut Studi Islam Sunan Doe, 2023)
This study aims to analyze the effect of profitability, complexity of operation, audit tenure and accounting firm public size on audit delay in manufacturing companies listed on the IDX in 2019-2021. The analytical method used in this study is Multiple Linear Regression Analysis. The results of research on the effect of profitability, operational complexity, audit tenure, and KAP size on audit delay in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period, concluded: profitability has a negative effect on audit delay, complexity of operation does not have influence on audit delay, audit tenure has no effect on audit delay, and accounting firm public size has a negative effect on audit delay.